The effects of a cycling warm-up including high-intensity heavy-resistance conditioning contractions on subsequent 4-km time trial performance - Chorley, A.; Lamb, K. L. (The Journal of Strength and Conditioning Research, 2019)
Previous exercise has been shown to improve subsequent performance through different mechanisms. Sport-specific conditioning contractions can be used to exploit the "post-activation potentiation" (PAP) phenomenon to enhance performance although this has rarely been investigated in short endurance events. The aim of this study was to compare a cycling warm-up with PAP-inducing conditioning contractions (CW) with a moderate-intensity warm-up (MW) on performance and physiological outcomes of a 4-km time trial. Ten well-trained male endurance cyclists (VO2max 65.3 ± 5.6 ml/kg/min) performed two 4-km cycling time trials after a 5-minute recovery after a warm-up at 60% of VO2max for 6.5 minutes (MW), and a warm-up with conditioning contractions (CW) consisting of 5 minutes at 60% of VO2max then 3 × 10-second at 70% of peak power interspersed with a 30-second recovery. Blood lactate concentrations were measured before and after time trial. Expired gases were analyzed along with time, power output (PO), and peak forces over each 500 m split. After CW, mean completion time was reduced (1.7 ± 3.5 seconds p > 0.05), PO increased (5.1 ± 10.5 W p > 0.05) as did peak force per pedal stroke (5.7 ± 11 N p > 0.05) when compared with MW. VO2 increased (1.4 ± 1.6 ml·kg-1·min-1 p = 0.05) after CW, whereas respiratory exchange ratio (RER) decreased (0.05 ± 0.02 p = 0.05). Physiological and performance differences after CW were greatest over the first 1,500 m of the trials. The results suggest that a PAP-inducing warm-up alters VO2 kinetics and can lead to performance improvements in short endurance cycling but work and recovery durations should be optimized for each athlete.